Spontaneous Breathing Trial with 5 and 10 minutes in Very Low Birth Weight Infants: randomized controlled trial (Research, Society and Development, 2022)
This clinical trial aimed to evaluated the effects of a 5-minutes SBT and a 10-minutes SBT on successful extubation rates of very low birth weight (VLBW) infants compared to clinical judgment alone. A double-blind randomized controlled trial was conducted in two NICU in Alagoas, Brazil, including 88 VLBW infants allocated in three groups: control group, 5-minutes SBT and 10-minutes SBT. SBT was performed under endotracheal CPAP mode with 5 cmH2O positive end-expiratory pressure, inspiratory flow 10 L/min and FiO2 of 30%. The primary outcome was successful extubation rate, defined as no need for reintubation within 7 days after extubation. There was no difference among the three groups in relation to the proportion of successful extubation rate (p =0.644), bronchopulmonary dysplasia (BPD) (p =0.790) and hospital length stay (p = 0.175). To have passed the 5-minutes or the 10-minutes SBT did not improve successful extubation rates in VLBW infants compared to clinical judgment alone or made difference in BDP occurrence and hospital stay length. Designing a predictor test of extubation readiness in preterm infants remains a challenging in respiratory management.